EVALUATION OF ANTIDEPRESSANT ACTIVITY OF HERBOMINERAL FORMULATION - Patel, Snehal S.; Rajshree, Niti; Shah, Praboth V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: In the search for new therapeutic products for the treatment of neurological disorders, medicinal plant research, worldwide, has constantly progressed, demonstrating the pharmacological effectiveness of different plant species in a variety of animal models. SOBEREX CAPSULE (SC) is a herbomineral formulation used by ayurvedic practitioners for treatment of depression. The present study was designed to generate scientific evidence for SC in animal models of depression in mice. Methods: The formulation was administered orally to the mice at a dose of 50 mg/kg for 14 d, and at the end of treatment animals were subjected to tail suspension test and the forced swimming test in mice. Results: The effect of SC at the dose of 50 mg/kg was comparable to that of reference antidepressant fluoxetine. The formulation and fluoxetine, at the doses tested, produced no significant effects on locomotor activity. These results demonstrated that SC had antidepressant effects without side effect. Conclusion: Thus, SC possesses antidepressant-like effects in mice, providing further support for the traditional use of the formulation against central nervous disorders. Keywords: Antidepressant, Herbomineral formulation, Forced swim test, Tail suspension test